Dinobryon ningwuensis (Chrysophyta, Dinobryaceae), a new freshwater species described from Shanxi province, China - Jiang, Xiao-Die; Nan, Fang-Ru; Lv, Jun-Ping; Liu, Qi; Xie, Shu-Lian; Kociolek, John Patrick; Feng, Jia (Phytotaxa, 2018)
The new freshwater species of Chrysophyceae, Dinobryon ningwuensis is described from material collected from Pipahai Lake in Shanxi province, China. This new species is similar to D. sertularia, D. sociale and D. sociale var. americana in the shape of the lorica and organization of the colony. The cells have two heterokont flagella surrounded by a lorica and occurred both as free-living, solitary cells or in branched colonies. Our new species is characterized by having a cylindric lorica, wide and short, colonies are narrow and short in length. These features slightly differ D. ningwuensis from D. sertularia, D. sociale and D. sociale var. americana. In addition to describing the morphological structures of D. ningwuensis, a phylogenetic analysis based on sequences of the nuclear small subunit ribosomal DNA (SSU rDNA), internal transcribed spacer 1 (ITS1), 5.8S rDNA and the internal transcribed spacer 2 (ITS2) placed this alga in single clade with a considerable sequence distance from the other Dinobryon species. Thus, results of both morphological comparisons and phylogenetic analysis based on molecular data suggest this alga as a new species, increasing the total number of recognized freshwater Chrysophyta species in China.